2016
DOI: 10.17015/ejbe.2016.018.04
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Performance of Indian Exchange Traded Funds (ETFs)

Abstract: Exchange traded funds (ETFs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Following the existing literature (Rompotis, 2012 ; Reddy, 2012; Alam, 2013 ; Narend & Thenmozhi, 2016 ; Sethi, 2016 ; Malhotra et al, 2016 ; Singh & Kaur, 2016 ) we estimate the performance and tracking efficiency of the sample equity ETF’s.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the existing literature (Rompotis, 2012 ; Reddy, 2012; Alam, 2013 ; Narend & Thenmozhi, 2016 ; Sethi, 2016 ; Malhotra et al, 2016 ; Singh & Kaur, 2016 ) we estimate the performance and tracking efficiency of the sample equity ETF’s.…”
Section: Methodsmentioning
confidence: 99%
“…An Ordinary Least Square (OLS) regression is performed to resolve a set a of gripping issues (Prather et al, 2009 ; Rompotis, 2010 , 2012 ; Charupat & Miu, 2013 ; Sethi, 2016 ). As the results of Augumented Dickey Fuller test indicated that the returns of ETF’s and Indexes are stationary, OLS regression model can be carried out using the following equation: where R pt denote the sample ETF’s average raw return on day t , R bt represents average raw return of the underling benchmark on day t and residual error is denoted by ε pt .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A base de dados coletados utilizada para a realização deste trabalho foi obtida na plataforma Bloomberg, sendo composta pelos preços de fechamento diários das cotas dos fundos, valores diários de fechamento dos seus índices de referência e pelos valores diários de fechamento das cotas do valor patrimonial líquido dos referidos fundos, de 2 de dezembro de 2008 até 10 de setembro de 2018, perfazendo um total de 2.416 observações. Os cálculos foram feitos utilizando as ferramentas de análise e estatísticas do programa Microsoft Excel Modelo de identificação da estratégia de replicação Conforme aplicado porRompotis (2012) eSethi (2016), uma regressão simples é utilizada para desvendar uma série de elementos relevantes: Tracking Error Rompotis (2012) define o termo "tracking error" como os desvios nos retornos de produtos de investimentos geridos de forma passiva e os seus benchmarks, cujo…”
unclassified